Exact Solutions of the Vakhnenko-Parkes Equation with Complex Method - Yongyi Gu; Wenjun Yuan; Najva Aminakbari; Qinghua Jiang (Journal of Function Spaces)
We derive exact solutions to the Vakhnenko-Parkes equation by means of the complex method, and then we illustrate our main results by some computer simulations. We can apply the idea of this study to related nonlinear differential equation.